PENGARUH PARTISIPASI ANGGARAN PADA SENJANGAN ANGGARAN DENGAN KOMITMEN ORGANISASI DAN GAYA KEPEMIMPINAN SEBAGAI VARIABEL PEMODERASI - Yurika Mertayani, Ni Putu; Sadha Suardikha, I Made (E-Jurnal Akuntansi; Vol 20 No 3 (2017), 2017)
Budgetary slack is the difference in the reported budget amount by the number of best estimate of the organization. The purpose of this study was to determine the effect of budget participation on budgetary slack and to determine the role of organizational commitment and leadership style in relation budgetary participation and budgetary slack. The population in this study was 16 at the County Government Office of Tabanan to 45 the number of respondents, head of department, head of planning and chief financial officer. Sampling technique used in this study is saturated samples. The analysis technique used is multiple regression analysis and moderated regression analysis (MRA). The results obtained in that budget participation a positive influence on budgetary slack, organizational commitment does not weaken the influence of the budget on budgetary slack participation and leadership style weaken the influence of budget participation on budgetary slack.
Keywords: Participation Budgeting, Budgetary Slack, Organizational Commitment, Leadership Style